PROFESSIONAL GUIDANCE AND CAREER PLANNING: WORKSHOPS WITH INSTITUTIONALIZED DRUG ADDICTS - Rodrigues de Lima, Natália; Yvonne Spiendler Rodriguez, Sandra (Health and Society, 2023)
Chemical dependency is a public health problem, a disease that causes damage in several areas of the life of the subject who uses psychoactive substances. These losses may involve, in addition to health issues, family, school, financial and work aspects. The treatment of chemical dependency aims at social reintegration and this process is still a challenge for the population that suffers from this disease. Work is an activity of paramount importance in the lives of human beings and unemployment, for chemically dependent people, can aggravate their social exclusion. The absence of work possibilities is constant in subjects in a situation of dependence, since the difficulties of managing daily responsibilities alongside chemical dependence often culminate in breaking the bond with work. Bearing in mind that the number of drug addicts in Brazil and in the world is growing and that work occupies a central place in people’s lives, interventions that allow the rescue of social insertion through work can be assertive to prevent relapse in the treatment. Given the above, the present study is qualitative, descriptive and observational. The objective of this study was to identify the importance of a Professional Orientation and Career Planning process in the treatment of institutionalized chemical dependents. The study included 6 men over 18 years old, who were hospitalized in a Hospital Complex in Mental Health, located in the city of Canoas/Rio Grande do Sul. Data were collected through workshops focused on Professional Guidance and Career Planning that addressed self-knowledge and training of these individuals for stages of selection processes. The analysis of the collected data was carried out in the light of a thematic analysis. The results indicate that the process of professional guidance and career planning carried out contributed to the treatment of participants by promoting mental health, helping in the treatment of chemical dependence and serving as a strategy in preventing relapse. New studies on the subject are suggested through interventions carried out in Therapeutic Communities (TC), since the length of stay is longer.